If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.3 + x = 6.1 Solving 2.3 + x = 6.1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.3' to each side of the equation. 2.3 + -2.3 + x = 6.1 + -2.3 Combine like terms: 2.3 + -2.3 = 0.0 0.0 + x = 6.1 + -2.3 x = 6.1 + -2.3 Combine like terms: 6.1 + -2.3 = 3.8 x = 3.8 Simplifying x = 3.8
| 2.54+1.50= | | M^2-12m+96=-4 | | 1+2u=9 | | 4q-6=2 | | 2+4q=10 | | 6(v-6)-2=-7(-3v+5)-9v | | -4m=92 | | 5k+6=321 | | 1+3s=10 | | 6+5(2y-2)=-6(2y-1)+8y | | 5f-10=10 | | 3.9e+11= | | -3x=9/4 | | 3-8x^2=-29 | | 3x-(2y+x)-y= | | -3/5y=-9 | | 20=10x+15x | | 5x-7+10=5x+3 | | 7/3=5n/6 | | 3/2y=18 | | 3sin^2x-2cosx-2=0 | | 5x-20=7x+5 | | 5=4x+2x | | 3+3x+5=5x | | 10$/0.04ct | | 8x^7(2x^7-9x^2)= | | 2-7x=-2x+2 | | -1x+3=6x-4 | | 7.9e+8= | | x^3-11.9=-3.3 | | 2+7x=-7x-166 | | 6+y+y^2=26 |